2007
DOI: 10.1016/j.socscimed.2007.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Transactional sex with casual and main partners among young South African men in the rural Eastern Cape: Prevalence, predictors, and associations with gender-based violence

Abstract: We explored the prevalence and predictors of transactional sex with casual partners and main girlfriends among 1,288 men aged 15-26 from 70 villages in the rural Eastern Cape province of South Africa. Data were collected through face-to-face interviews with young men enrolling in the Stepping Stones HIV prevention trial. A total of 17.7% of participants reported giving material resources or money to casual sex partners and 6.6% received resources from a casual partner. Transactionally motivated relationships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
260
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(271 citation statements)
references
References 29 publications
11
260
0
Order By: Relevance
“…In South Africa, many people referred to schoolgirls using so-called sugar daddies (older men) to acquire key items like smart mobile phones. In southern Africa, where the pattern of girls having older sexual partners has been linked to HIV and AIDS risks, intimate relationships are conventionally intertwined with money or gifts (Bryceson and Fonseca 2006;Dunkle et al 2007;Poulin 2007). The implications of such liaisons for girls' school careers are rarely positive.…”
Section: Mobility and Autonomy: A Gender Perspectivementioning
confidence: 99%
“…In South Africa, many people referred to schoolgirls using so-called sugar daddies (older men) to acquire key items like smart mobile phones. In southern Africa, where the pattern of girls having older sexual partners has been linked to HIV and AIDS risks, intimate relationships are conventionally intertwined with money or gifts (Bryceson and Fonseca 2006;Dunkle et al 2007;Poulin 2007). The implications of such liaisons for girls' school careers are rarely positive.…”
Section: Mobility and Autonomy: A Gender Perspectivementioning
confidence: 99%
“…Transactional sex that is not sex work in the traditional sense, nor only an outcome of poverty, but is also fuelled by consumerist pressures to acquire goods and social status, as well as linked with culturally-based notions of gender, love and exchange (see Bhana & Pattman 2011;Hunter 2002Hunter , 2010, has also been shown to be common. Studies have indicated that transactional sexual relationships, especially when they involve a number of power dynamics including age and access to resources, play a significant role in unsafe, unequal and coercive sexual practices, and as a result are receiving increased attention in Africa (Clowes, Shefer, Fouten, Vergnani & Jacobs 2009;Dunkle, Jewkes, Brown, Gray, McIntyre & Harlow 2004;Dunkle, Jewkes, Nduna, Jama, Levin, Sikweyiya, et al 2007;Hallman 2004;Kaufman & Stavros 2004;Leclerc-Madlala 2003;Maganja, Maman, Groves & Mbwambo 2007;Masvawure 2010;Ulin 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Young people are usually financially and materially motivated to engage in these types of relationships. They receive gifts, money, clothes food, cosmetics, cash and clothing and other resources in exchange of sex) [15]. These relationships come with varying levels of commitment because in most instances these sugar dads and moms are engaged in relationships with other partners and will not invest in their relations with young people [16,17].…”
Section: Discussionmentioning
confidence: 99%